Perturbation theory for operational quantum non-Markovianity - Bonifacio, Mariano (2020)
The definition of memory in operational approaches to quantum non-Markovianity depends on the statistical properties of different sets of outcomes related to successive measurement processes performed over the system of interest. Using projector techniques we develop a perturbation theory that enable to expressing both joint probabilities and outcome correlations in terms of the unperturbed system density-matrix propagator. This object defines the open system dynamics in the absence of measurement processes. Successive series terms, which are scaled by the system-environment interaction strength, consist in a convolution structure involving system propagators weighted by higher-order bath correlations. The formalism is corroborated by studying different dynamics that admit an exact description. Using the perturbative approach, unusual memory effects induced by the interplay between the system-environment interaction and measurement processes are found in finite temperature reservoirs.